Web 2.0 for fostering students' social presence in online learning-based interaction - Yahya Al-dheleai; Zaidatun Tasir (OmniaScience, 2019)
Research in education confirmed that students engage in learning when they feel connected with others and when they play an active role in their learning process. Therefore; social presence (SP) considered as an important component of effective learning in both face-face and online learning environment. Therefore, this study intended to investigate students' perception about SP when using Web 2.0 tool for learning-based interaction and the difference in their perception based on gender and number of the semesters of the study. The participants of this study were 71 postgraduate students in one of the Malaysian public universities. The quantitative methods of data collection and data analysis were used in this study. Therefore, the researcher employed survey method using Online Social Presence Questionnaire (OSPQ) to collect the data. The data were analyzed using SPSS software to find mean, standard deviation of students' perception of their social presence while using Web 2.0 tool for learning-based interaction. Independent sample t-test was used to find the difference in students perception based on their gender. Moreover, One-Way ANOVA was used to find the difference in students' SP perception based on their semester of the study. The findings of this study showed that students expressed high perception about their social presence on Web 2.0 tool. Nonetheless, male students perceived higher social presence on Web 2.0 tool than female students. However, there were not significant differences in students' perception of social presence neither based on the gender difference nor on the number of the semester of the study.